2022
DOI: 10.3390/su14020811
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Evaluation of a Step-Up DC–DC Converter with Dual Loop Controllers for Two Stages Grid Connected PV Inverter

Abstract: In this work, a non-isolated DC–DC converter is presented that combines a voltage doubler circuit and switch inductor cell with the single ended primary inductor converter to achieve a high voltage gain at a low duty cycle and with reduced component count. The converter utilizes a single switch that makes its control very simple. The voltage stress across the semiconductor components is less than the output voltage, which makes it possible to use the diodes with reduced voltage rating and a switch with low tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A comprehensive review of the different controllers used in these inner loops can be found in [33]. In this paper, a proportional resonant controller discussed in [34] is used in these loops due to its high tracking capability (sinusoidal references) and dynamic response. This PR controller is designed based on a Naslin polynomial while considering the dynamics of LCL filter.…”
Section: ) Zero Level Controllermentioning
confidence: 99%
“…A comprehensive review of the different controllers used in these inner loops can be found in [33]. In this paper, a proportional resonant controller discussed in [34] is used in these loops due to its high tracking capability (sinusoidal references) and dynamic response. This PR controller is designed based on a Naslin polynomial while considering the dynamics of LCL filter.…”
Section: ) Zero Level Controllermentioning
confidence: 99%
“…A comprehensive review of different controllers used in these loops (inner and outer) can be found in [34]. However, in this paper, a Proportional Resonant controller discussed in [35] is used in these loops due to its high tracking capability (sinusoidal references) and dynamic response. Furthermore, to make an MG mainly inductive, an impedance loop (with inductance L v ) is used [36].…”
Section: System Configuration and Primary Controlmentioning
confidence: 99%
“…By implementing a hierarchical and decoupled structure, this approach enables robust control. In cascade inner-outer control, the bandwidth of the inner loop is set at 5 to 10 times larger than the bandwidth of the outer loop [29]. The inner loop controller is designed to swiftly respond to and eliminate fast dynamic instabilities of the system [30].…”
Section: Introductionmentioning
confidence: 99%